Epigenetic mechanisms involved in methamphetamine addiction - Hang Wang; Xianghuan Dong; Maher Un Nisa Awan; Jie Bai (Frontiers Media S.A., 2022)
Methamphetamine (METH) is an illicit psychostimulant that is widely abused. The molecular mechanism of METH addiction is complicated and still unknown. METH causes the release of the neurotransmitters including dopamine, glutamate, norepinephrine and serotonin, which activate various brain areas in the central nervous system. METH also induces synaptic plasticity and pathological memory enhancement. Epigenetics plays the important roles in regulating METH addiction. This review will briefly summarize the studies on epigenetics involved in METH addiction.